A THERAPEUTIC APPROACH USING AUTOMATIC TRAINING EXERCISES AND THEIR EFFECT ON SOME PHYSICAL AND FUNCTIONAL VARIABLES FOR ATHLETES INFECTED WITH THE CORONA VIRUS - Dr. Shymaa Ridha Ali; Dr. Jian Abdullah Noori (Galaxy International Interdisciplinary Research Journal, 2023)
The aim of the research: Preparing automatic training exercises related to the therapeutic approach for athletes infected with Corona virus. And to identify the effect of the therapeutic approach using automatic training exercises on some physical and functional variables for athletes infected with the Corona virus. As for the research sample, it consisted of (5) athletes infected with Corona virus in Baghdad, according to the following division: (1) a basketball player from Al-Arabi Club, (1) a volleyball player from Sulaikh Club, (1) a handball player from Al-Zawraa Club, and (2) Two football players, one of them is Al-Shula Club and the other is Al-Karkh Club. And these patients are reviewers of Al-Yarmouk Teaching Hospital and Al-Imamain Al-Kadhimin Teaching Hospital (peace be upon them), and the experimental approach of one group with one design (before - post) was applied, and the curriculum was applied on the Zoom program. The pre-tests were taken, then the field experiment was conducted, then the post-tests were conducted after 12 weeks of the therapeutic approach, and the data were processed by the Spss program. The results were significant, so the researcher concluded these conclusions that the therapeutic approach using automatic training exercises had an effective effect on raising the level of physical variables (strength, explosive power, speed and flexibility). And the automatic training exercises had a clear effect on the improvement of the lungs and pulmonary capacity. The therapeutic program also affected the health of the injured athletes. Immunity and immune proteins were restored to the normal state that protects the body from external influences and viruses.